In the wrong place but perhaps at the right time: a cochlear implant electrode impinging on tympanic membrane - Salleh, Mohamad Najib; Nik Othman, Nik Adilah; Mansor, Suzana; Salehuddin, Zulkiflee; Sidek, Dinsuhaimi; Zakaria, Mohd Normani (Jaypee Brothers Medical Publishers (P) Ltd, 2023)
Aim: This case report demonstrates the incidental finding of a cochlear implant (CI) electrode impinging on the tympanic membrane (TM).